Deep Learning Classification of Unipolar Electrograms in Human Atrial Fibrillation: Application in Focal Source Mapping - Liao, Shun; Ragot, Don; Nayyar, Sachin; Suszko, Adrian; Zhang, Zhaolei; Wang, Bo; Chauhan, Vijay S. (Frontiers in Physiology, 2021)
Focal sources are potential targets for AF catheter ablation, but they can be time-consuming and challenging to identify when unipolar electrograms (EGM) are numerous and complex. Our aim was to apply deep learning (DL) to raw unipolar EGMs in order to automate putative focal sources detection. We included 78 patients from the Focal Source and Trigger (FaST) randomized controlled trial that evaluated the efficacy of adjunctive FaST ablation compared to PVI alone in reducing AF recurrence. FaST sites were identified based on manual classification of sustained periodic unipolar QS EGMs over 5-seconds. All periodic unipolar EGMs were divided into training (n=10,004) and testing cohorts (n=3,180). DL was developed using residual convoluted neural network to discriminate between FaST and non-FaST. A gradient-based method was applied to interpret the DL model. DL classified FaST with a receiver operator characteristic area under curve of 0.904±0.010 (cross-validation) and 0.923±0.003 (testing). At a prespecified sensitivity of 90%, the specificity and accuracy were 81.9% and 82.5%, respectively in detecting FaST. DL had similar performance (sensitivity 78%, specificity 89%) to that of FaST re-classification by cardiologists (sensitivity 78%, specificity 79%). The gradient-based interpretation demonstrated accurate tracking of unipolar QS complexes by select DL convolutional layers. In conclusion, our novel DL model trained on raw unipolar EGMs allowed automated and accurate classification of FaST sites. Performance was similar to FaST re-classification by cardiologists. Future application of DL to classify FaST may improve the efficiency of real-time focal source detection for targeted AF ablation therapy.